Evaluation of physicochemical and microbiological quality of drinking water in the distribution system of Dharan, Nepal - Khatiwada, Aasara; Chaudhary, Asmita; Limbu, Dhiren Subba; Maharjan, Bijaya Laxmi (Himalayan Journal of Science and Technology, 2022)
Dharan has been facing drinking water-related problems for a very long time now and this research was conducted in order to determine whether the quality of water being distributed throughout the city was one of them. Hence, 31 samples were taken from the drinking water distribution system of Dharan in the spring of 2022 for evaluating the physicochemical and microbiological quality of drinking water being distributed across the sub-metropolitan city. Though public knowledge and adequate management of watershed and reservoir premises were insufficient, the physicochemical characteristics were determined to be within the National Drinking Water Quality Standards (NDWQS) for drinking water with temperatures ranging from 23.6 °C to 25.6 °C, pH 7.7 to 8.5, conductivity 38.2 to 38.7 µS/cm, Dissolved Oxygen (DO) 7.7 to 9.0 mg/L, Biological Oxygen Demand (BOD) 0.8 to 1.8 mg/L, chloride 29.82 to 34.08 mg/L, nitrite 10 mg/L and ammonia <0.5 mg/L. However, the coliform bacteria levels were significant, with the highest TCC (Total Coliform Count) being 137 CFU/100mL, the highest FCC (Fecal Coliform Count) being 85 CFU/100mL and the highest TPC (Total Plate Count) being TMTC (Too Many To Count). The water was found to be unsafe to drink without disinfection treatments. It may be necessary to carry out treatment procedures like chlorination as advised by WHO (World Health Organization) as soon as possible while also taking into account the proper application of filtration techniques for distributing safe drinking water to the residents of Dharan.